L’artiste contemporain dans les musées d’ethnographie ou la « promesse » d’un commissariat engagé - Bawin, Julie (RACAR : Revue d'art canadienne / Canadian Art Review, 2018)
For over three decades, ethnographic museums have been engaged in a process of redefining both their missions and their collections. Forced to reinvent themselves, as well as develop exhibition strategies in response to post-colonial theory, many of these museums have adopted a self-critical attitude and invited artists to intervene in their collections. What do such practices reveal ? When artists turn their attention to the collecting, archiving, and exhibition practices of colonial museums, does it follow that their approach is more engaged ? By considering the first exhibitions of this kind, while also tracing the evolution of this phenomenon since the 1980s, this paper seeks to respond to these questions. It also strives to understand the specific nature of critical curating as it is practiced in museums that are, more than any others, loci for identity politics.